POLA KONSUMSI PANGAN RUMAH TANGGA PADA DESA PELAKSANA DAN BUKAN PELAKSANA PROGRAM PERCEPATAN PENGANEKARAGAMAN KONSUMSI PANGAN (P2KP) DI KABUPATEN PRINGSEWU - Meri Handayani; Wuryaningsih Dwi Sayekti; Raden Hanung Ismono (Lampung University, 2019)
This research aims to analyze the pattern of food consumption, the pattern of processed local food consumption, and factors that affected the pattern of household food consumption in Pringsewu district. This research was conducted by survey method. Location of this research was determined purposively in Margosari Village North Pagelaran subdistrict as program implementers and Mulyorejo Village Banyumas subdistrict are not program implementers. The amount of research samples in this research was as many as 74 households who were selected by simple random sampling. The data was collected in month of Apri-May 2017. The data was analyzed by descriptive statistic analysis, and verification analysis by demand consumption function model. The result showed that the amount of energy consumption of Margosari village was 5,474.17 kcal/household/day and household energy consumption of Mulyorejo village was 4,745.22 kcal/household/day with their Desirable Dietary Pattern (DDP) score 78.24 and 68.96. Fried bananas was locally processed food sources of energy consumed and have the largest consumption frequency. Cassava was a local food that has the most processed product. Most of household got the processed local food by making them self. The pattern of household food consumption in Pringsewu district was influenced by the household income and number of household’s member.Key words: consumtion pattern, Desirable Dietary Pattern (DDP) score, local food